2020
DOI: 10.1186/s12935-020-01315-7
|View full text |Cite
|
Sign up to set email alerts
|

The expression patterns and the diagnostic/prognostic roles of PTPN family members in digestive tract cancers

Abstract: Background: Non-receptor protein tyrosine phosphatases (PTPNs) are a set of enzymes involved in the tyrosyl phosphorylation. The present study intended to clarify the associations between the expression patterns of PTPN family members, and diagnosis as well as the prognosis of digestive tract cancers. Methods: Oncomine and Ualcan were used to analyze PTPN expressions. Data from The Cancer Genome Atlas (TCGA) were downloaded through UCSC Xena for validation and to explore the relationship of the PTPN expression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 58 publications
1
36
0
Order By: Relevance
“…The prognostic value of 11 identi ed hub DEGs that were analyzed using the R survival package (26). PROGgenesV2 (http://genomics.jefferson.edu/proggene/ lter.php) is a web resource that allows researchers to study the correlations between genes and overall survival (OS) in multiple cancers based on TCGA and GEO data (27).…”
Section: Prognostic Value Of Hub Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…The prognostic value of 11 identi ed hub DEGs that were analyzed using the R survival package (26). PROGgenesV2 (http://genomics.jefferson.edu/proggene/ lter.php) is a web resource that allows researchers to study the correlations between genes and overall survival (OS) in multiple cancers based on TCGA and GEO data (27).…”
Section: Prognostic Value Of Hub Genesmentioning
confidence: 99%
“…P<0.05 was considered to be statistically signi cant. In addition, we downloaded 33 cancer expression pro les with associated mutation data from TCGA, and assessed the association between the prognosis-related hub genes and TMB (26,34).…”
Section: Immune Cell In Ltration and Tmb Analysismentioning
confidence: 99%
See 1 more Smart Citation
“… 11 A considerable amount of literatures indicated that PTPN18 is involved in the progression of various cancers. PTPN18 is correlated with the pathological grade in digestive tract cancers 12 and independent prognostic factors in hepatocellular carcinoma. 13 The expression of PTPN18 increased in breast tumor, illustrating that PTPN18 might be a critical mediator in oncogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…9 Among them, PTP nonreceptor type 1 (PTPN1, also known as PTP1B) has been revealed to be overexpressed in esophageal carcinoma, which was closely associated with incidence. 10 PTPN1 has been reported to be strongly associated with the development of various tumors, such as non-small cell lung cancer, 11 breast cancer 12 and glioma. 13 However, it has not been intensively studied in CC.…”
Section: Introductionmentioning
confidence: 99%